PUSTAKAWAN MEMANDANG KNOWLEDGE MANAGEMENT - Sudarsono, Blasius; Imadianti, Prafita (BACA: Jurnal Dokumentasi dan Informasi, 2012)
It is already more than a decade that the word of Knowledge Management (KM) have been discussed by librarians within the International Federation of Library Associations (IFLA). Many librarians then became interested in studying KM in order to implement it in their organizations. The discussions about KM then become broad and have been expanded into some fields, including tacit knowledge, implicit knowledge, explicit knowledge, and procedural knowledge. The crucial dimension of KM is collecting and connecting, so that dissemination of knowledge in organization becomes broader and deeper than before. This paper discusses the perception of Indonesian librarians toward KM.